Elimination of olfactory sensory neurons by zinc sulfate inoculation prevents SARS-CoV-2 infection of the brain in K18-hACE2 transgenic mice - Ji-Hun Lee; Eun-Seon Yoo; Na-Won Kim; Won-Yong Shim; Han-Bi Jeong; Dong-Hyun Kim; Young-Jun Park; Sun-Min Seo; Jun-Won Yun; Jun Won Park; Kang-Seuk Choi; Ho-Young Lee; et al. (Scientific Reports)
Abstract Coronavirus disease-2019 (COVID-19), attributed to the severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2), has posed global health challenges since it first emerged in 2019, and its impact continues to persist. The neurotropic nature of SARS-CoV-2 remains undisclosed, though researchers are proposing hypotheses on how the virus is transmitted to the central nervous system. One of the prevailing hypotheses is that SARS-CoV-2 travels through the olfactory nerve system via the olfactory epithelium (OE). Using a K18-human angiotensin converting-enzyme 2 (hACE2) transgenic mouse model with impaired olfactory sensory neurons (OSNs) induced by zinc sulfate, we examined the role of the olfactory nerve in the brain invasion by SARS-CoV-2. Mice lacking OSNs exhibited reduced levels of viral transmission to the brain, leading to significantly improved outcomes following SARS-CoV-2 infection. Moreover, a positive correlation was observed between viral persistence in the OE and brain infection. These results indicate that early inhibition of the olfactory nerve pathway effectively prevents viral invasion of the brain in K18-hACE2 mice. Our study underscores the significance of the olfactory nerve pathway in the transmission of SARS-CoV-2 to the brain.